Beginning HTML, XHTML, CSS, and JavaScript - Duckett, Jon (Hoboken, N.J Wiley Chichester John Wiley [distributor], 2010)
Provides instructions on creating a basic Web page and includes information on enhancing the site by using CSS, JavaScript, and XHTML
Chapter 1: Structuring Documents for the Web -- Chapter 2: Links and Navigation -- Chapter 3: Images, Audio, and Video -- Chapter 4: Tables -- Chapter 5: Forms -- Chapter 6: Frames -- Chapter 7: Cascading Style Sheets -- Chapter 8: More Cascading Style Sheets -- Chapter 9: Page Layout -- Chapter 10: Design Issues -- Chapter 11: Learning JavaScript -- Chapter 12: Working with JavaScript -- Chapter 13: Putting Your Site on the Web -- Chapter 14: Checklists
"Programmer to programmer."
Includes index
1
Keywords: Cascading style sheets; Cascading style sheets; HTML (Document markup language); Internet software; JavaScript (Computer language); JavaScript (Computer program language); Web site development; Web sites -- Design; XHTML (Document markup language); XHTML (Document markup language); Cascading Style Sheets; HTML; JavaScript; Programmierung; XHTML